Effects of low bar avoidance and gymnast size on high bar dismount performance - Sheets, A.; Hubbard, M. (ISB Congress, 2005)
Required maneuver difficulty on the uneven parallel bars has increased with the maximum allowed bar spacing. Computer modeling, simulation and optimization are used to quantify theb low bar`s detrimental effect on the maximal number of dismount revolutions a short and a tall gymnast can complete. Two optimal low bar avoidance strategies were calculated; 1) using only planar shoulder and hip movement (2D), and 2) using planar shoulder but three dimensional hip motion (3D).